Textile machinery and accessories - Rings and travellers for ring spinning and ring twisting frames : - International Organization for Standardization (ISO) (ISO)
ISO 96-2:2009 specifies the principal dimensions of HZ- and J-rings, and the mass and tolerance on the mass, of the appropriate travellers for HZ- and J-rings employed on ring spinning and ring twisting machines. It also specifies the method of designation of the travellers